An Analysis of Disability in Higher Education: A Canadian and Black Feminist Perspective - Bicknell-Hersco, Prilly (YU-WRITE: Journal of Graduate Student Research in Education, 2025)
In Canada, institutions of higher education are deeply rooted in colonial systems of knowledge production, institutionalized racism, and Eurocentric academic traditions. Despite the dismantling of formal legal barriers, Black disabled students continue to be marginalized by the legacies of racism and ableism embedded in academic policies, prevailing attitudes, and institutional cultures. Though there has been significant research focused on understanding the specific barriers faced by disabled students in higher education, much research is still needed on the intersecting challenges encountered by Black disabled women. This paper critically evaluates the essay Being Black and Disabled in University (Métraux, 2023) which draws on a study from Joy Banks, & Michael S. Hughes (2013), and responds to it within a Canadian context, employing a Black feminist disability studies framework. By integrating statistics and findings from the report on The Intersection of Blackness & Disability in Canada (Anderson, 2020) alongside the theoretical insights of Black feminist scholars and disability scholars, this paper foregrounds the nuanced realities of Black disabled students in higher education and advocates for systemic change so that we may implement tangible strategies to better support their experiences and academic outcomes.